2023
DOI: 10.3390/ijms242115792
|View full text |Cite
|
Sign up to set email alerts
|

Role of UBE2C in Brain Cancer Invasion and Dissemination

Stefani Domentean,
Eunice Paisana,
Rita Cascão
et al.

Abstract: Glioblastoma (GB) and brain metastases (BM) are the most common brain tumors in adults and are invariably associated with a dismal outcome. These highly malignant tumors share common features including increased invasion and migration of the primary or metastatic brain cancer cells, whose triggering mechanisms are largely unknown. Emerging evidence has suggested that the ubiquitin-conjugating enzyme E2C (UBE2C), essential for controlling cell cycle progression, is overexpressed in diverse malignancies, includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 125 publications
(190 reference statements)
0
2
0
Order By: Relevance
“…Moreover, most of the immune‐related markers and metabolism‐related pathways were associated with UBE2C expression level in THCA 50 . In hepatocellular carcinoma, UBE2C was found to be positively correlated with the infiltration of regulatory T cells and T follicular helper cells 52 . In renal cell carcinoma, UBE2C is strongly correlated with the infiltration of various immune cells, including M0 macrophages, regulatory T cells, and CD4+ memory T cells in RCC.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Moreover, most of the immune‐related markers and metabolism‐related pathways were associated with UBE2C expression level in THCA 50 . In hepatocellular carcinoma, UBE2C was found to be positively correlated with the infiltration of regulatory T cells and T follicular helper cells 52 . In renal cell carcinoma, UBE2C is strongly correlated with the infiltration of various immune cells, including M0 macrophages, regulatory T cells, and CD4+ memory T cells in RCC.…”
Section: Discussionmentioning
confidence: 92%
“…In adrenocortical carcinoma, UBE2C expression is positively linked with T helper Th1 and Th2 cells and negatively correlated with Treg, M2 macrophages 30 . Although UBE2C overexpression has been linked to immune cell infiltration in various cancer types, it may differ depending on the cancer type and require further investigation 50,52,54 . Acting as an oncogene in these cancers, UBE2C plays a crucial role in both cancer development and therapy, suggesting its potential as an effective therapeutic target for pan‐cancer.…”
Section: Discussionmentioning
confidence: 99%
“… 31 Notably, cells exhibiting UBE2C overexpression display a disregard for mitotic spindle checkpoint signals, resulting in compromised genomic stability—a hallmark characteristic of cancer. 32 Indeed, UBE2C expression is commonly observed to be upregulated in the realm of malignancies and hematologic disorders, displaying a direct association with heightened tumour proliferation and aggressiveness. Our research confirmed these findings in GC.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, a gene commonly upregulated in both drug-resistant 3D models was UBEC2C, which encodes for ubiquitin-conjugating enzyme 2C. This gene was found overexpressed and has been associated with chemotherapy resistance in several tumor types, including breast (reviewed in [30]). In the paclitaxel-resistant spheroids, we also detected the overexpression of SLIT2 (Figure 4a), a secreted glycoprotein that plays an important role in axon guidance and neuronal migration.…”
Section: Differential Gene Expression Analysis Of the Scrna-seq Data ...mentioning
confidence: 99%